2015
DOI: 10.1007/s10802-015-0030-y
|View full text |Cite
|
Sign up to set email alerts
|

A Community Study on the Relationship of Posttraumatic Cognitions to Internalizing and Externalizing Psychopathology in Taiwanese Children and Adolescents

Abstract: A growing number of studies indicate that posttraumatic cognitions play a crucial role in the development and maintenance of posttraumatic stress disorder (PTSD). However, the effects of posttraumatic cognitions on general psychopathology beyond PTSD remain unclear. The current study aimed to validate the Chinese version of the Child Posttraumatic Cognitions Inventory (CPTCI-C) and to investigate the relationship between posttraumatic cognitions and psychopathology. A community sample of 285 school-aged childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
19
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 25 publications
8
19
1
Order By: Relevance
“…The moderate correlations between dysfunctional cognitions and externalizing symptoms in our study were slightly stronger than in studies which had assessed proxy-reported externalizing symptoms [14, 16]. Again, discrepancies between self-reports and proxy-reports might be one reason for the slightly different results.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…The moderate correlations between dysfunctional cognitions and externalizing symptoms in our study were slightly stronger than in studies which had assessed proxy-reported externalizing symptoms [14, 16]. Again, discrepancies between self-reports and proxy-reports might be one reason for the slightly different results.…”
Section: Discussioncontrasting
confidence: 89%
“…In contrast, studies comparing dysfunctional cognitions with parent-reported internalizing problems found smaller correlations [14, 16]. Discrepancies between self-reports and proxy-reports are in line with the literature [49].…”
Section: Discussionsupporting
confidence: 67%
“…The significant cross-sectional correlations at each assessment, in line with our second hypothesis, confirmed previous findings on the association between dysfunctional posttraumatic cognitions and PTSS (see Mitchell, Brennan, Curran, Hanna, & Dyer, 2017) as well as their association with internalizing and externalizing problems (Leeson & Nixon, 2011;Liu & Chen, 2015). They are also in line with the findings reported in a nationally representative German sample in which youth affected by violence showed both internalizing and externalizing mental health problems, and they also exhibited significantly higher rates of cumulative mental health problems (Schlack & Petermann, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have demonstrated that post-traumatic cognitions are predictive of the severity and chronicity of PTSD symptoms (Hitchcock, 2015;Liu & Chen, 2015;Ma et al, 2011;Palosaari et al, 2013;Ponnamperuma & Nicolson, 2016), and may play an influential role in the maintenance of PTSD. In a longitudinal study with war-exposed Palestinian children aged 10-12 years, Palosaari et al (2013) found that high levels of post-traumatic cognitions at 3 months post exposure to trauma significantly predicted a worsening of PTSD symptoms 5 and 11 months post-trauma.…”
Section: Distorted Cognitions About the Trauma And Negative Beliefs/ementioning
confidence: 99%